2022
DOI: 10.1038/s41598-022-15293-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single cell and spatial transcriptomics reveal autoreactive differentiated B cells in joints of early rheumatoid arthritis

Abstract: B cells play a significant role in established Rheumatoid Arthritis (RA). However, it is unclear to what extent differentiated B cells are present in joint tissue already at the onset of disease. Here, we studied synovial biopsies (n = 8) captured from untreated patients at time of diagnosis. 3414 index-sorted B cells underwent RNA sequencing and paired tissue pieces were subjected to spatial transcriptomics (n = 4). We performed extensive bioinformatics analyses to dissect the local B cell composition. Select… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
15
5
Order By: Relevance
“…A further study of newly diagnosed, untreated RA patients assessed just under 2000 B cells from 3 RA patients, 2 of whom were seronegative for antibodies directed at citrullinated autoantigens (i.e., ACPA -ve ). Here there was no enrichment of ITGAX +ve (encoding CD11c) or CD27 -ve IgD -ve B cells (44). The difference between these observations and our study may relate to the early stage of RA and the limited number of B cells assessed with the predominance of ACPA -ve RA donors in that study.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…A further study of newly diagnosed, untreated RA patients assessed just under 2000 B cells from 3 RA patients, 2 of whom were seronegative for antibodies directed at citrullinated autoantigens (i.e., ACPA -ve ). Here there was no enrichment of ITGAX +ve (encoding CD11c) or CD27 -ve IgD -ve B cells (44). The difference between these observations and our study may relate to the early stage of RA and the limited number of B cells assessed with the predominance of ACPA -ve RA donors in that study.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, having clonal families containing diverse combinations of B cell subsets including both naïve B cells and ASCs suggests that the immunological response is local to the joint and naïve cells are migrating to the joint where they then become activated. This is supported by another single cell sequencing study of rheumatoid synovial B cells, which identified that over 50% of the plasma cells were derived from clonal families that also contained memory B cells (44). DN2 cells express CD11c, that is driven by the expression of the transcription factor T-bet.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Autoreactivity of ASCs in RA was also probed with tagged-ACPA, and showed that a subset of CD20 -CD138 + ASCs residing outside EGCs were producing autoantibodies (111). Autoreactivity against ACPA was further confirmed with the recombinant antibody technology (112). These ASCs in RA lesions were probed t be nonsusceptible to rituximab treatment (113).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Data regarding BAFF-R, TACI and BCMA expression on ASCs at the protein level are missing. However, BCMA and TACI has been described in ASCs from synovial tissues at the mRNA level ( 112 ).…”
Section: Organ-specific Diseasesmentioning
confidence: 99%